Impact of Value Added Tax on Total Tax Revenue Generating in Nepal - Surya Prasad Poudel (Journal of Islamic Economics Perspectives, 2025)
Government revenue is based for national development, social securities, national defense etc. VAT is a major source of government revenue in later period in the world because it has principles of transparency, tax to destination and theory of neutrality and economic growth. The objective of this study was to identify the impact of VAT on total tax revenue generation of Nepal. The 20 years panel data since 2001/002 to 2020/021 has been taken from governments’ publications and analyzed on the helps of mean, standard deviation, correlation and ridge regression. The multicollinearity in panel data has been removed by the helps of ridge VIF analysis. The mean and standard deviation of VAT has been found highest among other sources of revenue custom tax, excess duty and direct tax. However ridge regression analysis has shown weak impact of VAT on revenue generation rather than direct tax, custom tax, and excise duty. The government should increase VAT revenue by minimizing schedule of zero VAT rate goods and services, threshold of transactions etc.